The Use of Social Media in Adolescents as a Trigger for Bullying Behavior: A Study on High School Students in Bogor - Ratih Siti Aminah; Permana, Restiawan (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2024)
Bullying that occurs at the high school level is very urgent to get an immediate solution. This is considering that high school students are potential successors to development. Indonesia will enter the golden period, in 2045. Adolescents who are free from bullying will be ready to participate in development. Internet media is one of the triggers for bullying. Therefore, it is very important to know the use of adolescent internet media in relation to bullying.This study analyzes the relationship between adolescent social media use and bullying behavior among high school students in Bogor City. Data was collected from 100 respondents with an age range of 17-19 years, consisting of 57% women and 43% men. The analysis showed a significant relationship between adolescent characteristics and communication with peers (β = 3.225), as well as a relationship between adolescent characteristics and social media use (β = 1.835). In addition, a relationship was also found between adolescent characteristics and bullying behavior (β = 0.780). These results underscore the importance of paying attention to factors such as adolescent characteristics and interaction with social media in understanding bullying behavior among adolescents. These findings highlight the need for a holistic approach to the prevention and management of bullying behaviors that includes parental supervision as well as a better understanding of adolescents' social media use. Social media has a significant role in shaping adolescents' attitudes regarding bullying, family communication contributes to the occurrence of bullying behavior in adolescents.